2014
DOI: 10.3923/pjbs.2014.860.863
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Assessment in Malaria, Typhoid and Malaria-Typhoid Co-Infection in Aba, Abia State, Nigeria

Abstract: Malaria and typhoid fever are among the most endemic diseases in the tropics and are associated with poverty and underdevelopment with significant morbidity and mortality. Both diseases can lead to liver damage if not properly treated. The liver function assessment was therefore conducted on (90) volunteer patients; comprising (30) patients with malaria only, (30) with typhoid only and (30) with malaria-typhoid co-infection randomly selected from Abia State University Teaching Hospital, Aba, Abia State, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The increase in enzyme activities could be attributed to assaults on liver parenchymal cells by the malaria parasites leading to the leakage of the liver enzymes into the general circulation. This finding is in agreement with the study carried out by Enemchukwu et al [5] who reported that patients with untreated malaria parasite have high levels of ALT, AST and ALP in their blood. The finding also correlated with findings of previous studies of Mosab et al [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in enzyme activities could be attributed to assaults on liver parenchymal cells by the malaria parasites leading to the leakage of the liver enzymes into the general circulation. This finding is in agreement with the study carried out by Enemchukwu et al [5] who reported that patients with untreated malaria parasite have high levels of ALT, AST and ALP in their blood. The finding also correlated with findings of previous studies of Mosab et al [15].…”
Section: Discussionsupporting
confidence: 93%
“…The liver has a wide range of functions including detoxification, protein synthesis, production of biochemicals necessary for digestion, storing of glycogen and hormone production [5]. These functions are mostly enzymatic involving various classes of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated liver enzymes in malaria patients could be the result of leakage of the enzymes from the damaged liver cells during the hepatic stage of the life cycle of malarial parasite. Enemchukwu et al in 2014 suggested that typhoid, malaria and typhoid-malaria combined-infections can increase AST, ALT and ALP serum levels and result in liver damage if not treated properly 22 .…”
Section: S90mentioning
confidence: 99%
“…"Generally, fever is the most common cause of consultations in the tropics and sub-Saharan Africa where most fever are of infectious origin of which typhoid accounts for a majority. Typhoid fever is among the most endemic diseases in the tropics, it is associated with poverty and development with significant morbidity and mortality" [6]. "The emergence of multidrug resistance to the commonly used antibiotics has further complicated the treatment and management of enteric fever and this is recognized as one of the greatest challenges in the management of this disease The disease is an indication of neglect of control of the environment, while it is going extinct in the wider world, the case in Africa remains an alarming one as it is being recorded to constitute a major cause of hospital admissions in Africa" [7].…”
Section: Introductionmentioning
confidence: 99%